Antecedents and consequences of work-family conflicts: Italian women entrepreneurs' experiences. (17th March 2021) - Poggesi, Sara; Mari, Michela; Vita, Luisa De
This paper aims at unveiling the work-family conflict construct experienced by women entrepreneurs, by testing an all-inclusive model that considers work and family antecedents and consequences of WFC. The study is grounded on Europe and data from 511 Italian women entrepreneurs have been collected mailing a survey of 45 multiple choice questions. Opposing arguments either for the within and cross-domain hypotheses in relation to antecedents, or for the matching and cross-domain hypotheses in relation to the WFC consequences faced by women entrepreneurs have been tested. Findings show that the within-domain hypothesis is supported in relation to the antecedents as well as the matching and the cross-domain hypothesis in relation to the consequences. The contribution of this work is twofold: it enhances the understanding of women entrepreneurs' WFC; and it enriches the still limited and 'US centric' academic literature on the issue by analysing data collected in South Europe.